2019
DOI: 10.1155/2019/3489634
|View full text |Cite
|
Sign up to set email alerts
|

Multiresidue Pesticides Analysis of Vegetables in Vietnam by Ultrahigh-Performance Liquid Chromatography in Combination with High-Resolution Mass Spectrometry (UPLC-Orbitrap MS)

Abstract: An ultrahigh-performance liquid chromatography in combination with high-resolution mass spectrometry Thermo Q-Extractive Focus Orbitrap MS has been introduced for analysis of multiclass pesticides in vegetable samples collected in Hanoi, Vietnam. Multiclass pesticides were separated on the Thermo Hypersil Gold PFP column utilizing a gradient of the mobile phase consisting of 5 mM ammonium formate, 0.1% formic acid in deionized water, and methanol. The target analytes were detected in the full-scan mode on Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…These samples were then subjected for UPLC-MS/MS measurement. The peak area of target analyte was used to calculate the matrix effect, extraction recovery, and overall recovery as instructed by Vu-Duc et al [ 27 ]. The experimental results of matrix effect, extraction recovery, and overall recovery of all target compounds in both matrices are presented in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These samples were then subjected for UPLC-MS/MS measurement. The peak area of target analyte was used to calculate the matrix effect, extraction recovery, and overall recovery as instructed by Vu-Duc et al [ 27 ]. The experimental results of matrix effect, extraction recovery, and overall recovery of all target compounds in both matrices are presented in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, ME was compared using the signals of analytes in samples spiked after extraction (in sample matrix solution) and analytes in the “neat” solvent. The matrix effect, extraction efficiency, and overall recovery were calculated as Vu-Duc et al proposed [ 27 ]. Briefly, the ME, ionization enhancement, or suppression in mass spectrometry was assessed via postextraction spiking experiments.…”
Section: Methodsmentioning
confidence: 99%
“…To control the safe and efficient use of pesticides, their residues are regularly monitored in food and environmental samples in many countries according to risk-based sampling plans [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] or targeted surveillance with limited scope and sampling targets. For example, the world-wide activities are demonstrated with some selected publications from Argentina to Vietnam [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. In the European Union the largest number of residues tested within the EU-coordinated and national pesticide residue monitoring programs were reported in 2020 by Luxembourg (659), Malta (643), Germany (626), France (619) and Belgium (617) [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gas and liquid chromatography (GC and LC) mass spectrometry (MS) techniques are widely applied for the determination of pesticide residues in food products (Poma et al, 2019), particularly by applying the quick, easy, cheap, effective, rugged, and safe (QuEChERS) method (Anastassiades et al, 2003;Lehotay et al, 2010). On the other hand, in recent years several authors have demonstrated the importance of the ultrahigh-performance liquid chromatography and electrospray ionization quadrupole Orbitrap high-resolution (UHPLC/ESI Q-Orbitrap) mass spectrometry (MS) for the determination of pesticide residues in diverse samples of raw food products (Vu-Duc et al, 2019;Wang et al, 2019) and processed foods (Jia et al, 2014). All of these methods generate analytical responses called retention times (t R ) or retention indices (I).…”
Section: Introductionmentioning
confidence: 99%
“…This parameter considers the maximum (apex) of the peak belonging to a particular pesticide. The t R for a given compound is not fixed, since many factors affect its determination; for instance, the mobile phase flow rate, temperature differences in the oven and the column, as well as column length and column degradation (Vu-Duc et al, 2019).…”
Section: Introductionmentioning
confidence: 99%